Suppressing Voltage Fading of Li‐Rich Oxide Cathode via Building a Well‐Protected and Partially‐Protonated Surface by Polyacrylic Acid Binder for Cycle‐Stable Li‐Ion Batteries. Issue 15 (3rd March 2020) - Yang, Jingsong; Li, Peng; Zhong, Faping; Feng, Xiangming; Chen, Weihua; Ai, Xinping; Yang, Hanxi; Xia, Dingguo; Cao, Yuliang
Abstract: Li‐rich manganese based oxides (LRMOs) are considered an attractive high‐capacity cathode for advanced Li‐ion batteries; however, their poor cyclability and gradual voltage fading have hindered their practical applications. Herein, an efficient and facile strategy is proposed to stabilize the lattice structure of LRMOs by surface modification of polyacrylic acid (PAA). The PAA‐coated LRMO electrode exhibits only 104 mV of the voltage fading after 100 cycles and 88% capacity retention over 500 cycles. The structural stability is attributed to the carboxyl groups in PAA chains reacting with oxygen species on the surface of LRMO to form a uniform and tightly coated film, which significantly suppresses the dissolution of transition metal elements from the cathode materials into the electrolyte. Importantly, a H + /Li + exchange reaction takes place between the LRMO and PAA, generating a proton‐doped surface layer. Density functional theory calculations and experimental evidence demonstrates that the H + ions in the surface lattice efficiently inhibit the migration of transition metal ions, leading to a stabilized lattice structure. This surface modification approach may provide a new route to building a stable Li‐rich oxide cathode with high capacity retention and low voltage fading for practical Li‐ion battery applications. Abstract : Voltage fading of a Li‐rich oxide cathode is efficiently suppressed by using a polyacrylic acid (PAA) binder to build a well‐protected and partially‐protonated surface. The PAA‐coated Li‐rich manganese‐based oxides electrode exhibits only 104 mV of voltage fading after 100 cycles and 88% capacity retention over 500 cycles.